Performance of aqueous tetrabutylammonium hydroxide, piperazine and their blends for carbon dioxide capture - Safdar, R. (Elsevier B.V., 2018)
The potential of aqueous ammonium based IL, tetrabutylammonium-hydroxide (TBAOH), the aqueous tertiary amine, piperazine (PZ) and two aqueous solutions of TBAOH and PZ blend for CO2 capturing was estimated by solubility study. For this purpose, the experiments were carried at five different pressures and three temperatures by using a solubility cell. The experimentally obtained solubility data was used to determine Henry's constant which further used to estimate the enthalpy and entropy of the system. The overall results revealed that CO2 solubility in all the solutions is directly proportional to pressure but inversely proportional to temperature. The experimental solubility data was correlated with artificial neural network (ANN) modeling and predicted solubilities are reported. On comparison with literature, it was found that the TBAOH exhibited high CO2 solubility than many other solvents under same conditions of temperature, pressure and concentration. On the other side, the aqueous blends of TBAOH and PZ also showed promising results and CO2 solubility was higher in the low concentrated blends of TBAOH and PZ as compared with high concentration. Â© 2018